PERTANGGUNGJAWABAN KEJAHATAN KORPORASI DALAM TINDAK PIDANA EKONOMI MENURUT UNDANG-UNDANG DARURAT NOMOR 7 TAHUN 1955 - Bella Diana Putri (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2021)
The development of the business world in Indonesia is currently increasingly modern and sophisticated, where this development is followed by the development of a society that has a consumptive lifestyle, so that it becomes a trigger and impetus for business actors who commit crimes in the economic field. The subject of crime in the economic field is not only committed by individuals but also corporations. In this study there are two problems, namely (1). What is the liability of corporations in economic crimes according to the Emergency Law Number 7 of 1955? (2) What is the current criminal law policy regarding corporate criminal liability? The research method used is a normative legal research method with a statute approach, a comparative approach and an analytical and conceptual approach. The results of the research are (1) Corporate accountability in economic crimes according to the Emergency Law Number 7 of 1955 concerning Investigation, Prosecution, and Judiciary of Economic Crimes, regulated in Article 15. The policy of corporate responsibility in the UUTPE is also strengthened by the Supreme Court Regulation Number 13 2016 concerning Procedures for Handling Criminal Cases by Corporations. (2) The Criminal Code does not regulate corporations as the subject of criminal acts that can be accounted for in criminal law and several laws outside the Criminal Code have regulated corporations as subjects of criminal acts that can be accounted for in criminal law, but are still partial and inconsistent Keywords: Corporation, Economic Crime